Assessment of Zinc Alpha-2 Glycoprotein Level in Gestational Diabetes Woman in Respect to Glycemic Status with and without Treatment - Bara Nahdh Saleem; Manal Khalid Abdulridha; Hind Abdalkhaliq Showman; Manal Sabbar (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Background: Gestational diabetes is a pathological condition that manifests between the 2nd and 3rd trimesters of pregnancy. It is distinguished by substantial insulin resistance induced by the secretion of placental hormone. Adipocytes secrete a particular type of adipocytokine called zinc a2 glycoprotein (ZAG), and numerous reasearches have suggested that ZAG is involved in crucial physiological processes such as glucose metabolism.